Economics policies: Costa Rican economy in the face of unexpected shock - Suárez-Espinoza, Kerlyn (2021)
The aim of this paper is based on analyzing the Costa Rican economy in the face of covid-19 pandemic. For that purpose, it starts from the fact that the health measures imposed by governments produce effects on the economy.  Faced with this, some relevant indicators are set out, made by institutions like Instituto Nacional de Estadística y Censos or Costa Rica’s Central Bank; and some measures implemented on Costa Rica and the United States. The paper uses secondary information available about national or international authors and institutions. Positions of Joseph Stiglitz, Amartya Sen and Mariana Mazzucato are briefly presented as well as some economic policy measures with a sustainable and equitable vision as an opportunity to improve the current conditions.